Epiregulin as a therapeutic target in non-small-cell lung cancer - Sunaga N (Dove Medical Press, 2015)
Noriaki Sunaga,1,2 Kyoichi Kaira2,31Oncology Center, Gunma University Hospital, 2Department of Medicine and Molecular Science, 3Department of Oncology Clinical Development, Gunma University Graduate School of Medicine, Gunma, JapanAbstract: Epiregulin (EREG) belongs to the ErbB family of ligands. EREG binds to EGFR and ErbB4 receptor and stimulates homodimers of EGFR and ErbB4 in addition to all possible heterodimeric ErbB complexes, resulting in the activation of downstream signaling pathways. EREG is overexpressed in various human cancers and has been implicated in tumor progression and metastasis. Oncogenic activation of the MEK/ERK pathway plays a central role in the regulation of EREG expression. Non-small-cell lung cancers (NSCLCs) harboring KRAS, BRAF, or EGFR mutations overexpress EREG, and abrogation of such mutations or inhibition of MEK or ERK downregulates the expression of EREG. Elevated EREG expression in NSCLC is associated with aggressive tumor phenotypes and unfavorable prognosis, especially in oncogenic KRAS-driven lung adenocarcinomas. The finding that attenuation of EREG inhibits cell growth and induces apoptosis in KRAS-mutant and EREG-overexpressing NSCLC cell lines suggests that targeting EREG might be a treatment option for KRAS-mutant NSCLC, although further studies are necessary to elucidate its therapeutic value. These observations suggest that oncogenic mutations in the EGFR, KRAS, or BRAF genes induce EREG upregulation through the activation of MEK/ERK pathway in NSCLC cells, whereas overproduced EREG stimulates the EGFR/ErbB receptors and activates multiple downstream signaling pathways, leading to tumor progression and metastasis of these oncogene-driven NSCLCs. This paper reviews the current understanding of the oncogenic role of EREG and highlights its potential as a therapeutic target for NSCLC.Keywords: epiregulin, NSCLC, KRAS mutation, therapeutic target